The Relevance of Educational Thoughts by Al-Kindi, Al-Farabi, and Ibn Sina in Contemporary Context - Sholeh, Muh Ibnu; Mohamed, Mohamed Ramadan Abd Allah; Ali, Himad; Ho, Pham Vu Phi (Asosiasi Ahli Filsafat Keilahian Indonesia, 2025)
This research investigates their similarities and differences in educational approaches and their relevance in modern educational contexts. The research method employs library research, drawing data from their works and philosophical perspectives on education, sourced from books, Google Scholar, ResearchGate, BASE, Publish or Perish, and Scopus. The data were analysed using data reduction, collection, and conclusion drawing. The result reveals that Al-Kindi emphasises reason and rational thinking, and Al-Farabi focuses on character formation and wisdom. At the same time, Ibn Sina views education as a holistic process encompassing intellectual, moral, and physical development. The implications underscore the importance of integrating these concepts into curricula and practices to prepare a knowledgeable, morally grounded, and wisely discerning future generation capable of navigating the complexities of the 21st century.